Thermodynamic analysis of single slope solar still using graphite plates and block magnets at seasonal climatic conditions - R. Dhivagar (IWA Publishing, 2021)
In this research, the thermodynamic (energy and exergy) analysis of a single slope solar still using graphite plates and block magnets (GPBMSS) was investigated during summer and winter climatic conditions of Coimbatore city (latitude: 11°01′68′′N and longitude: 76°95′58′′E), in India, 2019. The results observed in GPBMSS were compared with a conventional solar still (CSS) under the same climatic conditions. The outcomes observed that the hourly productivity in GPBMSS was 19.6% and 22.8% higher in summer and winter days, respectively, when compared to CSS. The cumulative productivity in GPBMSS was found to be about 3.93 kg/m2 and 3.56 kg/m2 respectively, for 12 h observations during summer and winter days. Furthermore, the energy and exergy efficiencies of GPBMSS were substantially improved by 20.6% and 18.1% when compared to CSS during summer days. Similarly, the energy and exergy efficiencies of GPBMSS were increased by 18 and 19% compared to CSS in winter days. In addition, the maximum basin exergy destruction was observed in CSS compared to other solar still components. The results observed that the heat storage ability of the graphite plates and water magnetization in GPBMSS greatly decreased the exergy destructions. Finally, the water quality analysis proved that the distillate collected from both GPBMSS and CSS satisfied the requirements recommended by the Bureau of Indian Standards. HIGHLIGHTS Graphite plates and block magnets are attached in a solar still basin (GPBMSS) and improved the productivity by 3.93 kg/m2 and 3.56 kg/m2 respectively, in summer and winter climatic days.; The energy efficiency of GPBMSS was substantially improved by 20.6 and 18%, respectively, compared to CSS during summer and winter days.; The exergy efficiency in GPBMSS was enhanced by 18.1 and 19%, respectively compared to CSS in summer and winter days.;